2006
DOI: 10.1016/j.asieco.2006.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Deficits, debt financing, monetary policy and inflation in developing countries: Internal or external factors?

Abstract: This paper focuses on internal and external factors, which influence the inflation rate in developing countries. A monetary model of inflation rate, capable of incorporating both monetary and fiscal policies as well as other internal and external factors, was developed and tested on three developing countries: Egypt, Iran and Turkey. The model performed well on the data of these countries. It was found that government debt and deficits along with other factors are important determinants of inflation. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 67 publications
3
36
0
6
Order By: Relevance
“…There have been a considerable number of studies on the link between budget deficits and inflation since the 1980s in developed countries and especially since the early 1900s in developing countries and emerging economies, when many of them implemented expansionary fiscal policy to speed up their economic growth (Barnhart, W.S., and Darrat, F.A., 1988;Bradley, D.M., 1984;Burdekin, C.K.R., and Wohar, E.M., 1990;Haan, J.D., and Zelhorst, D., 1990;Kia, A., 2006;Jeitziner, B., 1999). These studies, however, produced mixed results across countries and across periods of time, and have mainly concentrated on South American countries, Middle Eastern countries, Asian countries, and African countries.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There have been a considerable number of studies on the link between budget deficits and inflation since the 1980s in developed countries and especially since the early 1900s in developing countries and emerging economies, when many of them implemented expansionary fiscal policy to speed up their economic growth (Barnhart, W.S., and Darrat, F.A., 1988;Bradley, D.M., 1984;Burdekin, C.K.R., and Wohar, E.M., 1990;Haan, J.D., and Zelhorst, D., 1990;Kia, A., 2006;Jeitziner, B., 1999). These studies, however, produced mixed results across countries and across periods of time, and have mainly concentrated on South American countries, Middle Eastern countries, Asian countries, and African countries.…”
Section: Introductionmentioning
confidence: 96%
“…The empirical results show that the fiscal deficit had a strong impact on inflation in high-inflation periods, and had a weak impact in low-inflation episodes. Kia (2006) examined the determinants of inflation in Iran and found that the fiscal policy was quite effective to combat inflation, implying that that higher budget deficits cause inflation and vice versa; reducing budget deficits will contribute to fighting inflation. Another study by Ahmad and Sajad (2011) also for Iran found that there was not only the causation from budget deficits to inflation but also a direction from the price level to budget deficits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 Since the aim of this paper is to investigate the effect of stock prices on the nominal exchange rate and not to focus on potential effects of fiscal policy, debt deficit and debt management, the utility function employed does not incorporate government expenditure and risk associated with holding domestic money balances. For such specification see Kia (2006) and Wilson (2009). 12 A direct way to model the role of money in facilitating transactions would be to develop a time-shopping model after introducing leisure in the utility function.…”
Section: The Modelmentioning
confidence: 99%
“…where C t is real consumption of a composite bundle of goods, and foreign real money balances respectively, 0 < β < 1 is the individual's subjective time discount factor, σ, ε, X are assumed to be positive parameters, with 0.5 < σ < 1 and 0.5 < ε < 1, and E t (·) the mathematical conditional expectation at time t. For analytical tractability and following Kia's (2006) suggestion, we assume that , α, η 1 , and η 2 are all normalized to unity. The present value of lifetime utility is assumed to be maximized subject to a sequence of budget constraints given by: are real money balances expressed in current domestic unit terms (with M t − 1 and M * t−1 domestic and foreign nominal money balances respectively carried forward from last period), e t the nominal exchange rate defined as the amount of foreign currency per unit of domestic currency and P t the price index of the composite good consumed domestically.…”
Section: The Modelmentioning
confidence: 99%